The Village Regulation Development to Protect Mangrove Forest in Paluh Kurau Village - Harefa, Meilinda Suriani; Nur Rohim; Damanik, Muhammad Ridha; Matondang, Muhammad Farouq Ghazali (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2023)
Paluh Kurau Village is one of the villages in North Sumatra Province which has good mangrove forest potential and needs to be managed in a sustainable manner because it is also potentially threatened by the activities of the surrounding community. This study aims to determine the understanding of Paluh Kurau Community about the conditions and benefits of mangroves in Paluh Kurau and to draft village regulations to protect mangroves. The method in this study is descriptive qualitative and uses two types of data, namely primary data (field observations and interviews) and secondary data (literature review). Based on 30 respondents who were interviewed, 25 people (83%) answered that the condition of the mangrove forest in Paluh Kurau village had decreased due to changes in land use, namely, to become oil palm plantations, rice fields, settlements, and intensive ponds. The benefits of mangroves that are known to the community are as a water filter, oxygen producer, abrasion prevention, barrier to the entry of sea water into the mainland, and fish habitat as a source of livelihood. The development of village regulations includes agreements, policies, rights, obligations, prohibitions, and sanctions for protecting mangroves that refer to the national regulations of the Republic of Indonesia. The results of this study are important as a reference for protecting mangrove forests in Paluh Kurau Village and as a model for village-level mangrove forest protection policies that can be implemented in other areas